Electric-field-induced antiferromagnetic resonance in antiferromagnetic insulators with spin-orbit coupling - Akihiko Sekine; Takahiro Chiba (AIP Advances, 2017)
We study theoretically spin dynamics in three-dimensional antiferromagnetic insulators with spin-orbit coupling. We focus on the antiferromagnetic insulators whose low-energy effective model possesses a topological term called the θ term. By solving the Landau-Lifshitz-Gilbert equation in the presence of the θ term, we show that the antiferromagnetic resonance can be realized by ac electric fields along with static magnetic fields. The antiferromagnetic resonance can be detected via the spin pumping from the Néel field and net magnetization. We calculate both contributions to the pumped spin current, and find that the magnitude of the ac electric field to cause the resonance state is very small (∼ 1 V/m). This indicates that spin currents can be generated efficiently. The mechanism of the antiferromagnetic resonance in this study is understood as the inverse process of the dynamical chiral magnetic effect.